Liberare e federare L'eredità intellettuale di Silvio Trentin - Cortese, Fulvio (Carte, Studi e Opere - Centro Trentin di Venezia, 2016)
For many years, the figure of Silvio Trentin (1885-1944) had been forgotten. Then, between the Seventies and the Eighties, the profile of this highly original jurist, acknowledged as the protagonist of the vast and complex anti-fascist and resistance scene, began to attract the attention of many scholars. This volume, conceived on the occasion of the seventieth anniversary of Trentin's death, aims at offering an articulated portrait of the jurist, with focus on the peculiarities of his juridical formation, the tenacity of his political choices and the richness of his family relationships. The aim of the work is not only celebratory: it is a matter of giving back to the Italian Republic a strong witness of the many battles which preceded its birth, and which can still revive its reasons.